Genetic diversity and structure of Iberian Peninsula cowpeas compared to world-wide cowpea accessions using high density SNP markers - Márcia Carvalho; María Muñoz-Amatriaín; Isaura Castro; Teresa Lino-Neto; Manuela Matos; Marcos Egea-Cortines; Eduardo Rosa; Timothy Close; Valdemar Carnide (BMC Genomics, 2017)
Abstract Background Cowpea (Vigna unguiculata L. Walp) is an important legume crop due to its high protein content, adaptation to heat and drought and capacity to fix nitrogen. Europe has a deficit of cowpea production. Knowledge of genetic diversity among cowpea landraces is important for the preservation of local varieties and is the basis to obtain improved varieties. The aims of this study were to explore diversity and the genetic structure of a set of Iberian Peninsula cowpea accessions in comparison to a worldwide collection and to infer possible dispersion routes of cultivated cowpea. Results The Illumina Cowpea iSelect Consortium Array containing 51,128 SNPs was used to genotype 96 cowpea accessions including 43 landraces and cultivars from the Iberian Peninsula, and 53 landraces collected worldwide. Four subpopulations were identified. Most Iberian Peninsula accessions clustered together with those from other southern European and northern African countries. Only one accession belonged to another subpopulation, while two accessions were ‘admixed’. A lower genetic diversity level was found in the Iberian Peninsula accessions compared to worldwide cowpeas. Conclusions The genetic analyses performed in this study brought some insights into worldwide genetic diversity and structure and possible dispersion routes of cultivated cowpea. Also, it provided an in-depth analysis of genetic diversity in Iberian Peninsula cowpeas that will help guide crossing strategies in breeding programs.